DAMPAK KEADILAN ORGANISASI TERHADAP PERILAKU PROAKTIF: PERAN MEDIASI KETERIKATAN KERJA - Saleh, Hamdani; Abdillah, Muhammad Rasyid; Nasution, Imran Al Ucok (Komunitas Manajemen Kompetitif, 2025)
This study analyzes the effect of organizational justice on proactive behavior, with work engagement as a mediating variable, among non-permanent employees at the State Polytechnic of Bengkalis. Using a quantitative explanatory approach and Structural Equation Modeling with Partial Least Squares (SEM-PLS), data were collected from all non-permanent staff in laboratory, administrative, and technical roles. The results indicate that organizational justice significantly influences both work engagement and proactive behavior. Furthermore, work engagement mediates the relationship between organizational justice and proactive behavior. These findings highlight the importance of creating a fair work environment to enhance employee engagement and encourage proactive behavior, particularly among non-permanent staff.Non-permanent employees often face limited access to organizational resources and recognition, making perceived fairness a crucial determinant of their work engagement. When employees perceive high levels of justice, they are more emotionally and cognitively involved in their work, which fosters proactive behavior. Therefore, it is essential for management to ensure that all dimensions of organizational justice—distributive, procedural, interpersonal, and informational—are consistently applied. A fair and inclusive system not only enhances the contributions of non-permanent staff but also strengthens institutional effectiveness and sustainability. Keywords: Organizational Justice, Work Engagement, Proactive Behaviour